Agricultural mechanization in Honduras: characterization, challenges, and opportunities for maize, beans, and coffee production systems - Patiño Espejel, Joshua Esaú; Cabrera Meraz, Jeimy; Vásquez, Emil; McLean, Denisse; Leal González, Abel Jaime; Van Loon, Jelle (CIMMYT, 2025)
CIMMYT and Universidad Zamorano carried out a study across five departments of Honduras (Lempira, Copán, Intibucá, Olancho, and El Paraíso) to characterize farmers’ use of tools and machinery in maize, bean, and coffee systems, and to identify key challenges and opportunities for mechanization. In total, 112 structured surveys of farmers were conducted. This dataset includes the survey results, providing information about household and farm characteristics, crops grown and area per crop, plot location and topography (hillsides, plains, or mixed terrain), and the tools and machinery used in each operation, such as land preparation, planting, weeding, harvesting, and post-harvest. It also includes information about access to mechanization services, reasons for lacking machinery, perceived benefits of using machinery, and cropping cycle stages that need mechanization, among other details. This can help guide the design of mechanization pathways suited to smallholder conditions in Honduras.